The plot against the president : [compact disc, unabridged] / the true story of how Congressman Devin Nunes uncovered the biggest political scandal in US history - Smith, Lee, 1962- (Blackstone, 2019)
Investigative journalist Lee Smith uses his unprecedented access to Congressman Devin Nunes, former head of the House Intelligence Committee, to expose the deep state operation against the president--and the American people.